Financial Management Behaviour of Mobile Legend Gamers - Ikhsani, Ramadan Gilang; Asandimitra, Nadia (Technium Social Sciences Journal, 2022)
Financial management behaviour, specifically the ability of an individual to plan and budget, manage and control, supervise, search for, and allocate daily financial funds. The purpose of this study is to see how financial literacy, hedonistic lifestyle, income, self-control, and financial attitude affect financial management behaviour. The subject of this study is Mobile Legend Gamers in Indonesia, with a sample size of 170 people. This is known as explanatory research, and it employs a quantitative approach with the Structural Equation Model-AMOS program. The findings revealed that financial literacy, income, self-control, and financial attitude all have a significant impact on financial management behaviour. Meanwhile, the hedonistic way of life has no effect. This was discovered because the majority of the respondents were still in their teens and still lived with their parents, and the study’s limitations were related to the distribution of questionnaires, which was only done online. As a result, more research is needed to be able to distribute questionnaires both offline and online and to use the model. Various approaches to researching financial management behaviour.